Distribution of VTA Glutamate and Dopamine Terminals, and their Significance in CA1 Neural Network Activity. (15th October 2020) - Adeniyi, Philip A.; Shrestha, Amita; Ogundele, Olalekan M.
Highlight: VTA dopamine and glutamate terminals are mapped to specific anatomical layers in the DG, CA3, and CA1. The distribution of VTA dopamine presynaptic terminals is robust in the CA1 stratum oriens and reduces putative pyramidal burst firing. VTA glutamate terminals innervate all CA1 layers and promote burst firing in putative pyramidal units. Abstract: Reciprocal connection between the ventral tegmental area (VTA) and the hippocampus forms a loop that controls information entry into long-term memory. Compared with the widely studied VTA dopamine system, VTA glutamate terminals are anatomically dominant in the hippocampus and less understood. The current study employs anterograde and retrograde labeling of VTA dopamine and glutamate neurons to map the distribution of their terminals within the layers of the hippocampus. Also, functional tracing of VTA dopamine and glutamate projections to the hippocampus was performed by photostimulation of VTA cell bodies during CA1 extracellular voltage sampling in vivo . VTA dopamine terminals predominantly innervate the CA1 basal dendrite layer and modulate the firing rate of active putative neurons. In contrast, anatomical dominance of VTA glutamate terminals in the CA1 pyramidal cell and apical dendrite layers suggests the possible involvement of these terminals in excitability regulation. In support of these outcomes, photostimulation of VTA dopamine neurons increased the firing rate but not intrinsic excitability parameters for putative pyramidal units. Conversely, activation of VTA glutamate neurons increased CA1 network firing rate and burst rate. In addition, VTA glutamate inputs reduced the interspike and interburst intervals for putative CA1 neurons. Taken together, we deduced that layer-specific distribution of presynaptic dopamine and glutamate terminals in the hippocampus determinines VTA modulation (dopamine) or regulation (glutamate) of excitability in the CA1 neural network.